OUTCOME OF TRANS RECTAL ULTRASOUND GUIDED TWELVE CORE BIOPSY OF PROSTATE FOR THE DETECTION OF PROSTATE CANCER- A SINGLE CENTER EXPERIENCE - Waqas, Muhammad; Shohab, Durre; Khawaja, Mohammad Athar; Masood, Afifa; Iqbal, Muhammad Waqas; Akhter, Saeed (Journal of Ayub Medical College Abbottabad, 2017)
Background: This study was conducted to determine the outcome of trans-rectal ultrasound (TRUS) guided biopsy of prostate for the detection of prostatic carcinoma in a single tertiary care hospital in Pakistan. Methods: This is a retrospective study including three hundred and eighty-three patients who underwent trans rectal ultrasound guided biopsy of prostate in a single tertiary care hospital. Indications for biopsy were raised prostate specific antigen (PSA), abnormal digital rectal examination (DRE) and/or both. Twelve core biopsy of prostate was done. Results: The overall detection rate of prostate cancer was 59%. Prostate cancer detection in various PSA ranges of 0-3.99, 4-9.99, 10-19.99 and >20 ng/ml are 22.22%, 37.88%, 50.0% and 89.9%. PSA density >0.15ng/ml2 can diagnose 74.5% of patients with cancer. Prostate cancer detection rate based on abnormal DRE is 64.6% compared to 60.8% detected by PSA>4 ng/ml. Conclusion: In conclusion raised PSA, smaller prostate volume, abnormal DRE and raised PSA density are associated with greater chances of detection of prostate carcinoma. Keywords: Digital rectal examination; Prostate cancer; Prostate Specific antigen; Prostate volume, Trans rectal ultrasound